Significance of heat generation and thermophoretic particle deposition in Marangoni convective driven boundary layer flow of cross nanofluid with activation energy - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; Alhefthi, Reem K.; İnç, Mustafa (Elsevier, 2024)
The thermo-solutal Marangoni boundary layer flow has been studied because it has a number of real-world uses, such as drying silicon wafers, applying thin coats of paint or glue, employing adhesive in heat exchangers, and growing crystals in space. The physical phenomenon of Cross (FeSO4-(CMC-H2O(<0.4%)) nanofluid flow in a porous medium with thermophoretic particle deposition and Marangoni convective flow is explored. Non-Newtonian Cross nanofluid flow is explored in relation to the effect of activation energy. The process of thermophoretic particle deposition, which is important in both electrical engineering and aero-solution, is one of the most fundamental methods for transferring small particles across a heat gradient. Cross nanofluid containing FeSO4 as nanoparticle, and based fluid is (CMC- water). Using the appropriate similarity variables, the set of governing PDEs is transmuted into a set of ODEs. The RKF-45th method is used to numerically solve these simplified equations. The graphic examination of the concentration, velocity and thermal fields is developed for the embedded non-dimensional characteristics. By raising the Marangoni ratio parameter, the surface tension gradient gets stronger, causing the induced flows to get stronger through the liquid more effectively. The concentration and thermal profiles fall with an enhancement in Marangoni ratio parameter.
Keywords: Cross nanofluid; Variable thermal conductivity; Activation energy; Thermophoretic particle deposition; Marangoni convection